2012
DOI: 10.1111/j.1463-1326.2012.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of linagliptin: a pooled analysis of data from randomized controlled trials in 3572 patients with type 2 diabetes mellitus

Abstract: This pooled analysis shows that linagliptin is well tolerated, with a low risk of hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
74
1
3

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 43 publications
17
74
1
3
Order By: Relevance
“…Reassuring hepatic safety data have also been reported with linagliptin as shown in a meta-analysis of 8 placebo-controlled trials (Table 2) [48] . In the only study where a DPP-4 inhibitor (5 mg linagliptin) was administered once daily for 7 days in patients with mild and moderate HI, the DPP-4 inhibitor was well tolerated [47] .…”
Section: Hepatic Safetymentioning
confidence: 70%
See 2 more Smart Citations
“…Reassuring hepatic safety data have also been reported with linagliptin as shown in a meta-analysis of 8 placebo-controlled trials (Table 2) [48] . In the only study where a DPP-4 inhibitor (5 mg linagliptin) was administered once daily for 7 days in patients with mild and moderate HI, the DPP-4 inhibitor was well tolerated [47] .…”
Section: Hepatic Safetymentioning
confidence: 70%
“…However, it is always difficult to confirm a causal relationship in such observational reports because of the presence of many confounding factors [37] . Pooled analyses of large clinical trials with sitagliptin [34] , vildagliptin [40] and linagliptin [48] (Table 2) as well as data from the two recently published major cardiovascular outcome studies reporting liver safety data with saxagliptin [45] and alogliptin [53] (Table 3) are reassuring. On the contrary, some preliminary data suggested that inhibition of DPP-4 might be beneficial in CLD [74,75] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The safety profile of linagliptin has been analyzed in detail in previous dedicated reviews 24,69,70 and is generally good and quite similar to that previously reported with other DPP-4 inhibitors (i.e. almost comparable to that of placebo) 8,73,74 .…”
Section: Safety Evaluationmentioning
confidence: 64%
“…The safety profiles of each separate glucose-lowering agent, the biguanide compound metformin 4,49,50 or the DPP-4 inhibitor linagliptin 24,69,70 , are well documented. The most commonly reported adverse effects associated with metformin therapy are gastrointestinal, and include abdominal pain, diarrhea, nausea, and anorexia.…”
Section: Safety Evaluationmentioning
confidence: 99%